PENGARUH PERILAKU TERHADAP EFEKTIVITAS KOMUNIKASI MAHASISWA BIMBINGAN PENYULUHAN ISLAM UIN SYARIF HIDAYATULLAH JAKARTA - Sheyla Aulia Sagita; Nasichah Nasichah; Intan Alawiyah; Deva Nurfajrin; Syifa Ardila (Cross-border, 2023)
Effective communication plays an important role in education, especially in the field of Islamic Guidance and Counseling. In the world of Psychology, every human action is strongly influenced by several factors without these factors, humans cannot live effectively, especially in communication. Personal factors themselves are divided into 4 types, the first is biological factors, the second is affective factors, the third is cognitive factors, and the fourth is conative factors. In this article, we examine the influence of behavior on the effectiveness of student communication in Islamic guidance and counseling. The purpose of this study is to understand the relationship between students' communication behaviors and their communication effectiveness in an Islamic Guidance and Counseling environment. Behavioral factors include listening skills, clear language, empathy and cultural awareness. The researcher used descriptive quantitative research methods. The data collection technique used in this study is a specially developed questionnaire that measures the communication behavior and communication effectiveness of college students. The data were analyzed with the help of statistical analysis and the relationship between communication behavior and communication effectiveness was determined. Based on the results of the study, it can be seen that communication behavior, including feeling confident when communicating with others, paying attention to one's movements when communicating, feeling curious about what is conveyed, listening and paying attention when communicating with others, understanding when communicating, providing motivation/encouragement, communicating well despite emotions, giving trust when communicating, providing a way out, using body language when communicating, maintaining behavior when communicating, controlling tension and anxiety when communicating have a significant impact on the communication effectiveness of Guidance and Islamic Counseling students and tend to have higher communication effectiveness.